Large-scale complementary macroelectronics using hybrid integration of carbon nanotubes and IGZO thin-film transistors - Chen, Haitian; Cao, Yu; Zhang, Jialu; Zhou, Chongwu (Nature communications, 2014)
Carbon nanotubes and metal oxide semiconductors have emerged as important materials for p-type and n-type thin-film transistors, respectively; however, realizing sophisticated macroelectronics operating in complementary mode has been challenging due to the difficulty in making n-type carbon nanotube transistors and p-type metal oxide transistors. Here we report a hybrid integration of p-type carbon nanotube and n-type indium–gallium–zinc-oxide thin-film transistors to achieve large-scale (>1,000 transistors for 501-stage ring oscillators) complementary macroelectronic circuits on both rigid and flexible substrates. This approach of hybrid integration allows us to combine the strength of p-type carbon nanotube and n-type indium–gallium–zinc-oxide thin-film transistors, and offers high device yield and low device variation. Based on this approach, we report the successful demonstration of various logic gates (inverter, NAND and NOR gates), ring oscillators (from 51 stages to 501 stages) and dynamic logic circuits (dynamic inverter, NAND and NOR gates). Carbon nanotubes and metal-oxide semiconductors are widely used in thin-film transistors, but integrating the two technologies is challenging. Here, the authors report a hybrid integration of p-type carbon nanotubes and n-type IGZO transistors, resulting in a large-area complementary circuit.